2007
DOI: 10.1007/s10562-007-9186-6
|View full text |Cite
|
Sign up to set email alerts
|

Iodine a Simple, Effective and Inexpensive Catalyst for the Synthesis of Substituted Coumarins

Abstract: Molecular iodine is developed as an efficient catalyst in the von Pechmann condensation of phenols with b-ketoesters which leads to the formation of coumarin derivaties in excellent yields when carried out under microwave irradiation in a Prolabo Synthwave Microwave Reactor. The reaction also proceeds when carried out in the absence of solvent and at room temperature in acetonitrile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 32 publications
(19 reference statements)
1
19
0
Order By: Relevance
“…It is widely applied for the synthesis of coumarins. A large number of reagents were used for this reaction, including sulfuric acid, phosphorus pentoxide, aluminum chloride, trifluoroacetic acid, SnCl 2 [97], oxalic acid [98], alum (KAl(SO 4 ) 2 ·H 2 O, silica triflate, iodine, [99] etc., which are preferred for the reaction. Recently, a number of studies have also shown that ILs, either neutral [100] or acidic [101][102][103], promoted coumarin synthesis via the Pechmann condensation.…”
Section: Pechmann Reactionmentioning
confidence: 99%
“…It is widely applied for the synthesis of coumarins. A large number of reagents were used for this reaction, including sulfuric acid, phosphorus pentoxide, aluminum chloride, trifluoroacetic acid, SnCl 2 [97], oxalic acid [98], alum (KAl(SO 4 ) 2 ·H 2 O, silica triflate, iodine, [99] etc., which are preferred for the reaction. Recently, a number of studies have also shown that ILs, either neutral [100] or acidic [101][102][103], promoted coumarin synthesis via the Pechmann condensation.…”
Section: Pechmann Reactionmentioning
confidence: 99%
“…Lewis acids [6][7][8][9] , zeolites 10 , surfactants 11 , different types of nanoparticles 12,13 have also been employed to catalyze the reactions. Moreover, the uses of ionic liquids 14 , microwave 15,16 and ultrasound 17 are found in the recent literature to effect this condensation under ecofriendly conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Though a number of solvent-free methodologies are known for effecting Knoevenagel condensation 13,15,16,24 , only a few catalyst-free reaction conditions are reported 25,26 . Considering the importance of synthesis of new compounds containing an indole moiety and effecting Knoevenagel condensation under catalyst-and solvent-free conditions, we undertook the present work where 3-methylindole-2-carboxaldehyde (1) (readily available from a well-known indole compound skatole) 27 , with different active methylene compounds under the influence of heat only.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of condensing agents such as strong acids H 2 SO 4 , HCl, H 3 PO 4 , F 3 CCOOH, solid super acid [ 9 , 14 -16 ] [ 14 -18 ] and ion exchange resins [ 19 ] have been used in the Pechmann condensation. Recently, the use of microwaves [ 20 ], ionic liquid as a Lewis acid [ 21 ], Zn/I 2 [ 22 ], Yb(OTf) 3 [ 23 ], LiBr [ 24 ], I 2 [ 25 ], CoPy 2 Cl 2 [ 26 ], p-TSA [ 27 ], BTSA/SiO 2 [ 28 ] and polyvinyl sulfonic acid [ 29 ] has also been reported. Some of the above mentioned reagents possess limitations, such as the use of harsh or hazardous chemicals, mainly organic solvents, expensive and large amount of reactants, a longer reaction time, elevated temperature and the formation of side products.…”
Section: Introductionmentioning
confidence: 99%